Software Engineering: A Profession in Waiting. - Parnas, David Lorge (Computer (00189162), 2021)
Ongoing efforts to make software development an engineering discipline will fail until we have legislation requiring that creators of certain types of software be licensed, establishing a licensing authority, and detailing the capabilities that a licensed developer must possess.